FLUCTUATIONS OF THE OIL SARDINE FISHERY AT CANNANORE DURING 1961—1964 - Bensam, P (Indian Journal of Fisheries, 2011)
The decreasing trend in the catches of oil sardine at Cannanore from 1961-62 season leading to the total failure during 1963-64 and the remarkable recovery during 1964-65 are described. Information on the biology of the fish, based on the catches, such as maturity and feeding activities is briefly given. Observations on the behaviour of the fish in relation to certain environmental conditions have shown that temperature and salinity, perhaps, play a more significant role In the abundance of the population than factors like food or spawning. Juvenile oil sardine appear to have a narrower range of tolerance to temperature and salinity while the adults appear to have a wider range. Abudance of yearclasses in relation to their individual contributions to the fishery during each season has shown that the success or failure of the fishery in a given season depends upon the abundance of the juveniles recruited during that season. The probable causes for the failure of the fishery during 1963-64 and for the recovery during 1964-65 are discussed in the light of the data available.